2022
DOI: 10.3892/etm.2022.11275
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma piRNA array analysis and identification of possible biomarker piRNAs for the diagnosis of asthenozoospermia

Abstract: Asthenozoospermia (AZS) is characterized by reduced sperm motility and its pathogenesis remains poorly understood. Piwi-interacting RNAs (piRNAs) have been indicated to serve important roles in spermatogenesis. However, little is known about the correlation of piRNA expression with AZS. In the present study, small RNA sequencing (small RNA-seq) was performed on sperm samples from AZS patients and fertile controls. Reverse transcription-quantitative (RT-q) PCR was used to validate the small RNA-seq results. Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The piRNA expression studies on exosomes isolated from seminal plasma of asthenozoospermic patients reported downregulated piRNAs (piR-1207, piR-2107, piR-5937 and piR-5939) as the molecular biomarkers for male infertility [ 147 ]. Another study on seminal plasma of asthenozoospemic and normal healthy males identified 114 upregulated and 169 downregulated piRNAs, The top 10 upregulated piRNAs included piR-26,591, piR-32,694, piR-18,725, piR-16,782, piR-25,491, piR-5952, piR-18,611, piR-18,586, piR-15,811, piR-17,725 and top 10 downregulated piRNAs included piR-15,551, piR-29,529, piR-25,106, piR-2645, piR-9170, piR-2912, piR-23,203, piR-6148, piR-32,713, piR-29,155 [ 148 ].…”
Section: Generation Of Mirnasmentioning
confidence: 99%
See 2 more Smart Citations
“…The piRNA expression studies on exosomes isolated from seminal plasma of asthenozoospermic patients reported downregulated piRNAs (piR-1207, piR-2107, piR-5937 and piR-5939) as the molecular biomarkers for male infertility [ 147 ]. Another study on seminal plasma of asthenozoospemic and normal healthy males identified 114 upregulated and 169 downregulated piRNAs, The top 10 upregulated piRNAs included piR-26,591, piR-32,694, piR-18,725, piR-16,782, piR-25,491, piR-5952, piR-18,611, piR-18,586, piR-15,811, piR-17,725 and top 10 downregulated piRNAs included piR-15,551, piR-29,529, piR-25,106, piR-2645, piR-9170, piR-2912, piR-23,203, piR-6148, piR-32,713, piR-29,155 [ 148 ].…”
Section: Generation Of Mirnasmentioning
confidence: 99%
“…22 piRNAs were downregulated (<-1.5) in sperm sample of asthenozoospermic men when compared to normozoospermic men. He et al [ 148 ] 3 asthenozoospermic and 3 fertile controls Seminal plasma Small RNA sequencing Top 10 upregulated piRNAs: piR-26,591, piR-32,694, piR-18,725, piR-16,782, piR-25,491, piR-5952, piR-18,611, piR-18,586, piR-15,811, piR-17,725; top 10 downregulated piRNAs piR-15,551, piR-29,529, piR-25,106, piR-2645, piR-9170, piR-2912, piR-23,203, piR-6148, piR-32,713, piR-29,155. Cui et al [ 149 ] 186 infertile patients and 40 fertile controls Sperm qRT-PCR piR-31,704 and piR-39,888 were decreased in infertile group compared to control men.…”
Section: Generation Of Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…In men, microarray analysis revealed more than one hundred differentially expressed piRNAs in the sperm samples of asthenozoospermic patients compared to the normozoospermia cohort [ 58 ]. Among the significantly upregulated piRNAs, piR-26951 was predicted to target transcripts encoding flagella-associated protein 45 (CFAP45) and bromodomain-containing protein 2 (BRD2), both found to be differentially expressed in the sperm of patients with asthenospermia [ 59 , 60 ].…”
Section: Sperm Sncrna Transcriptome and Fecundity/fertilitymentioning
confidence: 99%